Respuesta :
4x - 5y = -12
-x + 5y = 18
-------------------add
3x = 6
x = 6/3
x = 2
4x - 5y = -12
4(2) - 5y = -12
8 - 5y = -12
-5y = -12 - 8
-5y = -20
y = -20/-5
y = 4
solution is (2,4) <==
-x + 5y = 18
-------------------add
3x = 6
x = 6/3
x = 2
4x - 5y = -12
4(2) - 5y = -12
8 - 5y = -12
-5y = -12 - 8
-5y = -20
y = -20/-5
y = 4
solution is (2,4) <==
4x - 5y= -12
-x + 5y= 18
-----------------add
3x = 6
x = 2
4x - 5y= -12
4(2) - 5y = -12
8 - 5y = -12
-5y = -20
y = 4
answer
(2, 4)
-x + 5y= 18
-----------------add
3x = 6
x = 2
4x - 5y= -12
4(2) - 5y = -12
8 - 5y = -12
-5y = -20
y = 4
answer
(2, 4)